2021
DOI: 10.3390/toxics9100245
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Polycyclic Aromatic Hydrocarbon Metabolites Are Associated with Biomarkers of Chronic Endocrine Stress, Oxidative Stress, and Inflammation in Adolescents: FLEHS-4 (2016–2020)

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are environmental pollutants of public health concern. Multiple biological mechanisms have been hypothesized to contribute to PAHs-associated adverse health effects. Little is known about the impact of PAHs on endocrine stress and inflammation in adolescence. We examined 393 Flemish adolescents (14–15 years) cross-sectionally, measured urinary concentrations of hydroxylated naphthalene, fluorene, phenanthrene and pyrene metabolites, and calculated the sum of all measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…They have also been related to neurodevelopment [8] and childhood asthma [9], yet the biological mechanisms through which PAHs exhibit such toxicity are still debated. PAHs have been reported to induce oxidative stress, in ammation and endocrine disruptions, which may each individually or jointly have adverse effects on the pregnancy [10][11][12]. Speci cally, PAHs can induce an excess of reactive oxygen species (ROS), which would target DNA, proteins and lipids, resulting in their oxidation [12].…”
Section: Discussionmentioning
confidence: 99%
“…They have also been related to neurodevelopment [8] and childhood asthma [9], yet the biological mechanisms through which PAHs exhibit such toxicity are still debated. PAHs have been reported to induce oxidative stress, in ammation and endocrine disruptions, which may each individually or jointly have adverse effects on the pregnancy [10][11][12]. Speci cally, PAHs can induce an excess of reactive oxygen species (ROS), which would target DNA, proteins and lipids, resulting in their oxidation [12].…”
Section: Discussionmentioning
confidence: 99%
“…18.5 ± 0.52 µmol mol −1 of creatinine for the age groups (12-20 years)), but, none of these studies could confirm a significant association [39,[46][47][48]. Three additional studies used a panel of PAH metabolites and reported a significant association [40,41,50]. Li et al [40], suggested, based on the observed urinary PAH profile, that exposure occurs mostly through inhalation and therefore depends on ambient AP, as the atmospheric PAH profile of low molecular weight OH-PAHs is very similar, whereas larger urinary PAH concentrations reflect additional sources such as diet.…”
Section: Correlation Between Internal Pah Metabolites Level and Early...mentioning
confidence: 93%
“…A similar trend has been observed in children [38-42, 46, 50, 53], children/adolescents [46], and adolescents [49], that is, an increase in AP is generally associated with an increase in the level of 8-OHdG or 8-oxodG in urine. It is worth mentioning that boys [8,41,50] might be more prone than girls [50], that the…”
Section: Epigenomic Associated Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The Flemish adolescents' spot urine samples investigated in this study were selected from the biobanked samples (n = 428, 14-15 years old adolescents; kept at -20℃) collected between September 2017 and June 2018 in the frame of the FLEHS IV reference biomonitoring study (2016-2020; approved by the Ethical Committee of the University Hospital of Antwerp, Belgium; Belgian Registry Number: B300201732753). The subset of samples (n = 83) were selected on the exposure load (high and low) calculated based on earlier quantitative analysis of 45 environmental chemicals (Buekers et al, 2021;Schoeters et al, 2022), such as phthalates and alternative plasticizers (Bastiaensen et al, 2021a), organophosphorus flame retardants (OPFRs) and plasticizers (Bastiaensen et al, 2021b), bisphenol analogues (Gys et al, 2021), and polycyclic aromatic hydrocarbon metabolites (Verheyen et al, 2021).…”
Section: Sample Collectionmentioning
confidence: 99%